Rasch Analysis And Driving Teachers' Self-Efficacy Of Arabic Language - Widayanti, Rizka; Annida, Alfika Syafa; Syah, Imas Jihan; Unsi, Baiq Tuhfatul; Ulinnuha, Muhammad Afthon; Musyafaah, Nurul (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2024)
This research aims to analyze the level of self-efficacy of Arabic teachers to become driving teachers. Researchers used a survey method. The data collection technique was carried out using a non-test instrument: a closed questionnaire containing three aspects of self-efficacy. The sample in this study was 14 Arabic teachers spread across Kediri Residency. The data analysis technique uses the Rasch Model, assisted by the Minister 5.6.1.0 application. The data findings show that the instrument's reliability is a logit figure of 0.98 (perfect) and a Cronbach Alpha logit figure of 0.90 (very high). The validity of the instrument shows that the average MNSQ (Mean Square) outfit is 1.02, and the average ZSTD (Z-standard) outfit is -0.3 (valid). Regarding instrument difficulty level, three statements are classified as easy, three as medium, ten as complex, and three as very difficult. Respondent R9P showed the highest respondent ability, while respondent R7L showed the lowest ability. Arabic teachers' magnitude, strength, and generality percentages are 79%, 74%, and 85%. The average percentage level of self-efficacy of Arabic teachers in Kediri residency is 91%, which is classified as very high)